Cellulose particles capture aldehyde VOC pollutants. Issue 13 (24th February 2020) - Bravo, Isaac; Figueroa, Freddy; Swasy, Maria I.; Attia, Mohamed F.; Ateia, Mohamed; Encalada, Domenica; Vizuete, Karla; Galeas, Salome; Guerrero, Victor H.; Debut, Alexis; Whitehead, Daniel C.; Alexis, Frank
Abstract : Cellulose particles isolated from biodiverse sources are capable of capturing aldehyde VOCs. Abstract : Aldehydes are commonly encountered Volatile Organic Compounds (VOCs) released to the atmosphere from a variety of anthropogenic sources. Based on the increasing interest in developing sustainable and environmentally friendly materials for the decontamination of VOCs, cellulose particles have emerged as one possible candidate, but there is a lack of understanding of the physicochemical properties affecting the adsorption of VOCs, and the effect of the extraction source on these intrinsic features. The present study was focused on the evaluation of unmodified cellulose particles extracted from biodiverse sources in Ecuador as potential VOC decontaminants. Modifications of the natural fibers with polyethylenimine (PEI) coating were performed to enhance the adsorption effectiveness. Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), Brunauer–Emmett–Teller (BET) measurements, and scanning electron microscopy (SEM) methods were used to characterize the physicochemical properties of the isolates. Gas chromatography assays demonstrated that unmodified cellulose can adsorb an aldehyde VOC, hexanal, reaching up to a 56.42 ± 7.30% reduction. Electrostatic coating of the cellulose particles with small quantities of PEI enhanced the VOC remediation capacities ( i.e. 98.12 ± 1.18%). Results demonstrated that the biodiverse plant source of the cellulose isolate can affect the gas capturing properties, and that these particles can be an environmentally friendly solution for effective adsorption of VOC pollutants.